2017
DOI: 10.1136/bmjopen-2016-015453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social deprivation on provision of bariatric surgery: 10-year comparative ecological study between two UK specialist centres

Abstract: ObjectiveTo investigate the effect of residential location and socioeconomic deprivation on the provision of bariatric surgery.DesignRetrospective cross-sectional ecological study.SettingPatients resident local to one of two specialist bariatric units, in different regions of the UK, who received obesity surgery between 2003 and 2013.MethodsDemographic data were collected from prospectively collected databases. Index of Multiple Deprivation (IMD 2010) was used as a measure of socioeconomic status. Obesity prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…The data from this study supports data from previous studies that patients of non-white ethnicity were at a higher risk of symptomatic COVID-19 postoperatively [33]. This may be due to several factors as non-white patients in this study come from countries with diverse healthcare systems and disease burdens [34]. Even within the same country, non-white populations may be at higher risk due to socio-economic and cultural factors.…”
Section: Discussionsupporting
confidence: 87%
“…The data from this study supports data from previous studies that patients of non-white ethnicity were at a higher risk of symptomatic COVID-19 postoperatively [33]. This may be due to several factors as non-white patients in this study come from countries with diverse healthcare systems and disease burdens [34]. Even within the same country, non-white populations may be at higher risk due to socio-economic and cultural factors.…”
Section: Discussionsupporting
confidence: 87%
“…37 A recent report from the Royal College of Surgeons also identified that 3% of Clinical Commissioning Groups have policies that do not follow national guidelines and subsequently restrict access to bariatric surgery. 38 Meanwhile, a recent analysis by Bhanderi et al 39 identified factors that may reduce access to bariatric procedures, including geographic variability and local deprivation. Reduction of such barriers to bariatric surgery would most likely therefore help improve all-cause mortality in the severely obese population in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Participants considered that the preoperative health behaviour change requirements to qualify for surgery were particularly demanding for Pacific patients who may live in more challenging socioeconomic situations compared with patients of other ethnicities. This is reflected in the wider literature investigating socioeconomic barriers to health in NZ19–22 38 and bariatric surgery utilisation in the UK, the USA, Canada, Australia and Sweden 2–5 39–41. Such patients are exposed to more obeseogenic factors and are less able to offset risk factors given higher financial pressures and lower education levels.…”
Section: Discussionmentioning
confidence: 99%